2007
DOI: 10.1672/0277-5212(2007)27[337:ticwic]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Constructed Wetlands (ICW) concept

Abstract: Wireless sensor networks have become incredibly popular due to the Internet of Things' (IoT) rapid development. IoT routing is the basis for the efficient operation of the perception-layer network. As a popular type of machine learning, reinforcement learning techniques have gained significant attention due to their successful application in the field of network communication. In the traditional Routing Protocol for lowpower and Lossy Networks (RPL) protocol, to solve the fairness of control message transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 16 publications
2
70
0
Order By: Relevance
“…This recalls the state of the art concept of integrated constructed wetland (ICW) reported by Scholz et al [19] , Harrington and McInnes [20] and Harrington and…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This recalls the state of the art concept of integrated constructed wetland (ICW) reported by Scholz et al [19] , Harrington and McInnes [20] and Harrington and…”
Section: Discussionsupporting
confidence: 81%
“…[21] Moreover, the incorporation of wetlands into the landscape enhances biodiversity. [19,20] Clearly, the ICW is a very important concept for the application of treatment wetland in urban area including urban lakes.…”
Section: Discussionmentioning
confidence: 99%
“…While it is appreciated that most of the systems are still relatively young and data may be insufficient, it is well noted that such modelling approaches cannot be done without, in line with current trends. Scholz et al, (2007) have however successfully applied the self-organizing Kohonen map as a novel modelling approach to some CWs data in Ireland with great success.…”
Section: Treatment Performancesmentioning
confidence: 99%
“…Twelve of the CWs treat farm effluent while one treats municipal wastewater. Scholz et al, (2007) reports that the principal design criteria leading to adequate effluent water quality (i.e., molybdate reactive phosphorus less than 1 mg/l) from the ICWs are that the wetland area needs to be sized by a factor of at least 1.3 times the farmyard area and the aspect ratio for the individual wetland segments needs to be less than 1:2.2 (width to length). It was further reported that within a year of the ICW commissioning, approximately 75% of farmyard runoff was intercepted, leading to improvements in the receiving surface waters of the catchment.…”
Section: The Irish Integrated Constructed Wetlands (Icws)mentioning
confidence: 99%
“…Steffenhagen et al (2012) demonstrate the important role of aquatic macrophytes for nutrient cycling in degraded, rewetted fens in Germany, suggesting that such vegetation can be used to accelerate the restoration of wetlands by facilitating low nutrient status. The concept of Integrated Constructed Wetlands (ICW) has attracted attention in recent years (Scholz et al, 2007) as it describes wetland systems that potentially provide multiple service benefits, including water cleansing, biodiversity enhancement, carbon storage and amenity. Two studies seek to develop the concept in this special issue.…”
mentioning
confidence: 99%